2012
DOI: 10.1152/japplphysiol.00770.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Ca2+ entry and cytoskeletal damage following eccentric contractions in mouse skeletal muscle

Abstract: Muscles that are stretched during contraction (eccentric contractions) show deficits in force production and a variety of structural changes, including loss of antibody staining of cytoskeletal proteins. Extracellular Ca(2+) entry and activation of calpains have been proposed as mechanisms involved in these changes. The present study used isolated mouse extensor digitorum longus (EDL) muscles subjected to 10 eccentric contractions and monitored force production, immunostaining of cytoskeletal proteins, and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 40 publications
4
47
0
3
Order By: Relevance
“…Our data are consistent with two other reports describing abnormal titin staining and reduced passive tension in WT muscle after lengthening contractions (31,34), as well as with the fact that titin fragmentation is detected in serum and urine, in dystrophindeficient mice as well as Duchenne muscular dystrophy patients (54)(55)(56). Disruption of the DGC is accompanied by compromised lateral force transmission (31,34). Thus, the excessive reduction in titin staining in muscles of the inducible DG KO mice may have been due to excessive strain on titin during contractions, when such transmission was disrupted.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data are consistent with two other reports describing abnormal titin staining and reduced passive tension in WT muscle after lengthening contractions (31,34), as well as with the fact that titin fragmentation is detected in serum and urine, in dystrophindeficient mice as well as Duchenne muscular dystrophy patients (54)(55)(56). Disruption of the DGC is accompanied by compromised lateral force transmission (31,34). Thus, the excessive reduction in titin staining in muscles of the inducible DG KO mice may have been due to excessive strain on titin during contractions, when such transmission was disrupted.…”
Section: Discussionsupporting
confidence: 93%
“…The extent of disruption of distinct components of the cytoskeleton/sarcomere may be unequal, as suggested by our finding that the expression of titin was disrupted by lengthening contractions whereas that of desmin, nebulin, and α-actinin was unperturbed. Our data are consistent with two other reports describing abnormal titin staining and reduced passive tension in WT muscle after lengthening contractions (31,34), as well as with the fact that titin fragmentation is detected in serum and urine, in dystrophindeficient mice as well as Duchenne muscular dystrophy patients (54)(55)(56). Disruption of the DGC is accompanied by compromised lateral force transmission (31,34).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…17 In addition, muscle from mdx mice with a dominant negative TRPC transgene show reduced Ca 2+ entry and less severe dystrophy 18 and muscle from TRPC1 knockout mice show less contraction-induced injury than wild-type muscle. 19 On the other hand, several studies show TRPV2 and TRPV4 contribute to Ca 2+ entry and stretch-induced injury in mdx muscle. 16,20 Evidently, the precise molecular identity of the MS channel responsible for Ca 2+ entry in dystrophic skeletal muscle remains uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this conclusion, there is good evidence for a role of TRPC1 in Ca 2+ entry and muscle damage in normal and dystrophic muscle from mdx mice. [17][18][19] These observations for a functional role of TRPC1 in the pathogenesis of dystrophin-deficiency suggest either TRPC1 acts as an independent source of Ca 2+ entry contributing to the dystrophic phenotype or that MS channels represent a novel variant formed by heteromeric subunit assembly TRPV4 subunits. 48,49 Ma et al showed TRPV4 and TRPC1 coassemble to form heteromeric TRPV4-C1 channels.…”
Section: Discussionmentioning
confidence: 99%